2015
DOI: 10.1002/ffj.3240
|View full text |Cite
|
Sign up to set email alerts
|

Optimization by response surface methodology of supercritical carbon dioxide extraction of flavour compounds from Chinese liquor vinasse

Abstract: Liquor vinasse is of interest under the biorefinery context and the aim of the present study was the recovery of flavour compounds. Supercritical carbon dioxide (SC-CO 2 ) extraction is an optimal method for liquor vinasse flavour compounds recovery. Gas chromatography with mass spectrometry analysis showed that more than 50 compounds were identified in the SC-CO 2 extract. The predominant compounds were esters and acids, and ethyl (9Z)-9-octadecenoate was the major ester. The effects of different extraction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Kumari et al (2016) reported the successful use of SC‐CO 2 extraction to separate residual phospholipids, a major contributor to off‐flavor generation in soymeal, compared to conventional defatting methods. The addition of ethanol to SC‐CO 2 extraction has been shown to enhance the separation of polar compounds, such as alcohols, phenolic compounds, terpenoids and carotenoids, from plant sources (Xu et al, 2015). Cocero and Calvo (1996) reported the use of SC‐CO 2 modified with ethanol for extracting sunflower oil from seeds.…”
Section: Approached To Minimize Flavor Of Protein Ingredientsmentioning
confidence: 99%
“…Kumari et al (2016) reported the successful use of SC‐CO 2 extraction to separate residual phospholipids, a major contributor to off‐flavor generation in soymeal, compared to conventional defatting methods. The addition of ethanol to SC‐CO 2 extraction has been shown to enhance the separation of polar compounds, such as alcohols, phenolic compounds, terpenoids and carotenoids, from plant sources (Xu et al, 2015). Cocero and Calvo (1996) reported the use of SC‐CO 2 modified with ethanol for extracting sunflower oil from seeds.…”
Section: Approached To Minimize Flavor Of Protein Ingredientsmentioning
confidence: 99%
“…The effective use of LW after bioethanol distillation has been investigated in various research fields, including conversion to biogas [6][7][8], application to animal and fish feed [9][10][11], and extraction of protein, pectin, and flavor compounds [12][13][14]. In agriculture, the potential use of LW from bioethanol distillation as a fertilizer has attracted much attention, and studies on the effects of its application on plants and soil have been conducted using LW from sugarcane [15][16][17] and beets [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Mystery behind Chinese liquor fermentation 33 fertilizer or culture substrate for edible mushrooms (Xu, Xu, Tao, Yuan, & Gao, 2015). Bioethanol production can be one of the possibilities to valorize liquor distillation wastes (Liu, Wu, Yang, Yuan, & Zhang, 2014;Tan, et al, 2014).…”
Section: Valorization Of Wastes and By-productmentioning
confidence: 99%
“…Recovery of flavor compounds from distilled solid waste is also attractive. By using supercritical carbon dioxide extraction, 55.17 g ethyl (9Z)-9octadecenoate per liter extract was obtained and can be used as solvent and food additive (Xu, et al, 2015). However, valorization of waste and by-product in Chinese liquor industry is still at a pioneering stage and the complex process causes inefficiency and embarrassment of the traditional industry.…”
Section: Valorization Of Wastes and By-productmentioning
confidence: 99%